Outsourcing, Occupationally Homogeneous Employers, and Wage Inequality in the United States - Handwerker, Elizabeth Weber (Journal of Labor Economics, 2023)
This paper develops measures of the occupational homogeneity of employers as indicators of outsourcing. Findings are threefold. First, wages are strongly related to occupational homogeneity, particularly for workers in low-wage occupations. Second, by some measures, workers—particularly those in higher-wage occupations—saw their employing establishments become more occupationally homogeneous during 2004–19. Third, changes in the occupational homogeneity of workplaces contributed to growing wage inequality among workers over the first part of this period. The growing sorting and segregation of workers by occupation into different employers is an important part of wage inequality.